2019
DOI: 10.1111/pce.13523
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of MADS‐box family genes during flower development in lettuce

Abstract: Lettuce (Lactuca sativa L.) is an important leafy vegetable consumed worldwide. Heat‐induced bolting and flowering greatly limit lettuce production during the summer. Additionally, MADS‐box transcription factors are important for various aspects of plant development and architecture (e.g., flowering and floral patterning). However, there has been no comprehensive study of lettuce MADS‐box family genes. In this study, we identified 82 MADS‐box family genes in lettuce, including 23 type I genes and 59 type II ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 61 publications
(74 reference statements)
7
46
0
Order By: Relevance
“…The lack of clear lettuce orthologs of FLC and SVP has made it difficult to form testable hypotheses regarding the regulatory mechanism through which ambient temperatures accelerate bolting in lettuce. In addition, two studies have reported binding motifs of heat shock transcription factors in the promoter regions of LsSOC1 and LsMADS55, putative lettuce orthologs to Arabidopsis SOC1 and APETALA1 (AP1), both known to function downstream of FLC in the floral induction pathway (Chen et al, 2018b;Ning et al, 2019). These reports postulate the possibility that the thermal control of flowering time in lettuce might have a different and more concise regulatory architecture than its counterpart in Arabidopsis.…”
Section: Ambient Temperature Pathwaymentioning
confidence: 99%
“…The lack of clear lettuce orthologs of FLC and SVP has made it difficult to form testable hypotheses regarding the regulatory mechanism through which ambient temperatures accelerate bolting in lettuce. In addition, two studies have reported binding motifs of heat shock transcription factors in the promoter regions of LsSOC1 and LsMADS55, putative lettuce orthologs to Arabidopsis SOC1 and APETALA1 (AP1), both known to function downstream of FLC in the floral induction pathway (Chen et al, 2018b;Ning et al, 2019). These reports postulate the possibility that the thermal control of flowering time in lettuce might have a different and more concise regulatory architecture than its counterpart in Arabidopsis.…”
Section: Ambient Temperature Pathwaymentioning
confidence: 99%
“…found many genes that were differentially expressed between two lettuce cultivars with different bolting time. The authors implicated a group of MADS-box and GA genes as owering regulators (Ning et al 2019). GA and related genes were shown to be related to bolting (Fukuda et al 2009; Umetsu et al 2011) speci cally in response to high temperatures (Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the lettuce plants begin to bloom and bear fruit. Previously, we characterized the inflorescence development of lettuce (Chen et al, 2017), and proposed a model for lettuce floral organ specification (Ning et al, 2019). Lettuce seeds are achene fruits that are developed from the ovaries.…”
Section: Introductionmentioning
confidence: 99%